MENDORONG PEMBIASAAN HIDUP BERSIH DAN SEHAT MELALUI KEGIATAN SENAM TERHADAP SISWA – SISWI MI NURUL ULUM II TEJA BARAT PAMEKASAN - Intan Saputri; Mustika Sari Dewi; Fahrur Rosi; Aditya Dyah Puspitasari; Ade Cyntia Pritasari; Ana Naimatul Jannah (STKIP Subang, 2025)
This community service activity at MI Nurul Ulum II Pamekasan aims to foster clean and healthy living habits through exercise activities. The main problems identified were the lack of regular sports activities and low student awareness of the importance of a healthy lifestyle. The program was implemented using demonstration and hands-on practice methods, where the service team introduced the benefits of exercise and guided students in performing the movements correctly. The results showed an improvement in students’ physical fitness, enthusiasm, and awareness of maintaining their health. This program proved effective in promoting clean and healthy living behavior (PHBS) within the elementary school environment